The Ottoman architecture in Greece then and now: Quantitative approach - Ahmed Ameen (Shedet, 2019)
Usually, of most studies on the Ottoman architecture in the Balkans are done by comparing between the numbers of buildings then and now. This paper discusses such method with regard to its comparative advantage and maximising its use in understanding Ottoman architecture. With Greece as a case study, the present paper identifies change in the quantity of Ottoman buildings considering the archetypal, functional, chronological, and geographical evidence, in the changing context of the nature of the Ottoman rule over centuries. The scholar provides new statistics presenting the numbers of Ottoman buildings in Greece over centuries, with special reference to three periods: the second half of the 17th century (time of EvliyâÇelebi), the late period of the Ottoman rule in Greece (based on Iyverdi’s statistics, the Ottoman slanames, and Kamûs-ülÂ'lâm of Şemseddin), and the existing architectural heritage in light of the recent publications and fieldworks’ results. Through statistical methods, this research identifies quantitative change of several types of buildings, proper to each region or in Greece as a whole.It observes the growth or decay of the pace of construction on the basis of three main factors: type of building, period, and region. The most significant results come from the comparison between the numbers of the Ottoman buildings in Greece dating to Evliyâ’s time at the end of the 17th century and the last decades of the Ottoman rule. The statistic table and the two charts with function and region indexes clarify to what extent the change in the number of buildings according to their function and region summarises the different phases of the Ottoman rule and the nature of each phase. The paper shows that the change in the numbers of buildings according to their function summarizes the alteration in nature of the Ottoman policy over the centuries, and the numbers of extant buildings strongly relate to the history and site of the corresponding regions. The paper clarifies that the reasons beyond the demolition of ottoman buildings in Greece include both human and natural factors, and concludes with a recommendation of preserving and reuse of extant ottoman structures.